2019
DOI: 10.1152/jn.00737.2018
|View full text |Cite
|
Sign up to set email alerts
|

D-type potassium channels normalize action potential firing between dorsal and ventral CA1 neurons of the mouse hippocampus

Abstract: Specific memory processes and neurological disorders can be ascribed to different dorsoventral regions of the hippocampus. Recently, differences in the anatomical and physiological properties between dorsal and ventral hippocampal CA1 neurons were described for both the rat and mouse hippocampus and have greatly contributed to our understanding of these processes. While differences in the subthreshold properties were similar between rat and mouse neurons, differences in action potential output between dorsal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
(135 reference statements)
4
21
0
Order By: Relevance
“…The properties of hippocampal pyramidal neurons vary along the dorsal ventral axis of the hippocampus (Dougherty et al 2012; Kim and Johnston 2015; Malik et al 2016; Ordemann et al 2019). More recently, OLM cells were shown to have distinct intrinsic physiological properties depending on the dorsal ventral location of the cell (Hilscher et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The properties of hippocampal pyramidal neurons vary along the dorsal ventral axis of the hippocampus (Dougherty et al 2012; Kim and Johnston 2015; Malik et al 2016; Ordemann et al 2019). More recently, OLM cells were shown to have distinct intrinsic physiological properties depending on the dorsal ventral location of the cell (Hilscher et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests the presence of a complicating factor in VHC neurons that disrupts the correlation between V thr at −65 mV and the max dV/dt . Interestingly, Ordemann et al have recently described a D‐type potassium current that depolarizes V thr in VHC neurons of the adult mouse hippocampus, and future work will be necessary to determine if a similar mechanism depolarizes V thr in rat VHC neurons (Ordemann, Apgar, & Brager, ).…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical properties of D-type K + channels allow them to act as high pass filters by depolarizing the voltage threshold for action potential generation in response to slow, but not fast, voltage trajectories. It was previously shown that current injections of variable duration can be used to separate the contribution of IKD to action potential threshold (Higgs and Spain, 2011;Kalmbach et al, 2015;Ordemann et al, 2019). Given that FMRP increases IKD in L5 ET, we expect that expression of FMRP will depolarize ET neuron action potential threshold for longer current injections.…”
Section: Viral Expression Of Fmrp Depolarizes Ap Threshold In L5 Et Nmentioning
confidence: 74%
“…This allows for a broader time window during which D-type channels can influence changes in membrane potential. D-type K + channels are enriched in the axo-somatic region of neurons where they oppose depolarization and exert strong influence over the threshold for action potential generation (Kole et al, 2007;Higgs and Spain, 2011;Ordemann et al, 2019). Changes in K + channel function contribute to neuronal hyperexcitability in neurological disorders such as epilepsy and episodic ataxia (Jan and Jan, 2012;Noebels et al, 2012;D'Adamo et al, 2020b).…”
Section: Introduction (388 Words)mentioning
confidence: 99%